Implementation of Standard Operating Procedures (SOP) in Improving Service Quality at the Sis Collection Jcity Medan Johor Cosmetics Store in 2025 - Siboro, Fidela Ahdawi; Simanungkalit, Rachel Charalita; Ayu, Senia Putri; Sembiring, Putri Sosanti (Generasi Sains Indonesia, 2025)
The current research focuses on the effectiveness of the implementation of Standard Operating Procedure (SOP) to improve service quality in Sis Collection, a cosmetics retailer located in the city of JCity Medan Johor, during the year 2025. The study follows a descriptive quantitative design, and data are gathered using a structured questionnaire that was given to five employees in the store. The domain of the study is to determine whether SOPs lead to efficiency, consistency, and customer satisfaction in day-to-day service delivery. The empirical evidence has shown that most of the employees view SOPs as useful in providing faster and more organized services, especially when dealing with customer complaints. Employees reported that SOPs minimize mistakes, provide a more orderly workflow and build confidence in working with customers. Nevertheless, there are still difficulties, since not all staff members said they were properly exposed to SOPs, and procedures were not actively communicated and enforced in a consistent way. Such gaps highlight the significance of ongoing training and regular distribution of SOP guidelines to maintain consistency in their usage throughout the organization. Overall, the findings suggest that SOPs have significant potential to improve the quality of service; however, their performance depends on their regular use and continued organizational investment in employees.